Dynamics Factors and Slow-Response Characteristics of Russian Trade Ties - SOPILKO, Natalya Yuryevna; NAVROTSKAIA, Natalia Anatolevna; KOVALEVA, Ekaterina Alexandrovna; ORLOVA, Angelika Feliksovna; GRIGORYEVA, Anna Vladimirovna (Journal of Advanced Research in Law and Economics, 2017)
Transformation of the world economy, new economic challenges, integration processes as a basis for international production cooperation require an in-depth study of international trade development. The aim of the research is modeling of trade ties of Russia and its key foreign economic partners and distinguishing crucial factors influencing dynamics of external trade flows. As part of the study we selected appropriate methods of econometric analysis of international trade dynamics in various branches. We used the following methods: a gravity model of mutual trade, a method of regressive decision trees, autoregression and a method of multidimensional adaptive regressive splines. We also distinguished crucial exogenous factors, influencing mutual trade of the researched countries. Having used various models, we found the most important determining factor for Russian foreign trade – prior period export (a system of international contracts). It can be explained by high transaction costs connected with new business- partners search and predominance of large long – term contracts in international trade. Using the concept of ‘specificity of assets’, we substantiated a response rate of international trade ties, which tend to be reproduced in former structural parameters as time goes by. It was proved that a response rate of international trade ties is characteristic for all researched countries.